2014
DOI: 10.1016/j.ajur.2014.08.007
|View full text |Cite|
|
Sign up to set email alerts
|

Prostate cancer in Asia: A collaborative report

Abstract: The incidence of prostate cancer (PCa) within Asian population used to be much lower than in the Western population; however, in recent years the incidence and mortality rate of PCa in some Asian countries have grown rapidly. This collaborative report summarized the latest epidemiology information, risk factors, and racial differences in PCa diagnosis, current status and new trends in surgery management and novel agents for castration-resistant prostate cancer. We believe such information would be helpful in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 147 publications
(107 citation statements)
references
References 69 publications
3
101
1
2
Order By: Relevance
“…When compared with other Asian countries this pattern is similar to that found in China, Hong Kong and Taiwan [6]. Whether this is due to the late presentation or due to an unknown risk factor is debatable [8].…”
Section: Total 193supporting
confidence: 55%
See 2 more Smart Citations
“…When compared with other Asian countries this pattern is similar to that found in China, Hong Kong and Taiwan [6]. Whether this is due to the late presentation or due to an unknown risk factor is debatable [8].…”
Section: Total 193supporting
confidence: 55%
“…In Asia prostate carcinoma is the sixth most frequent cancer in men [6]. Most prostate cancers (59.8%) in Sri Lanka still presents at the metastatic age similar to other South Asian countries and Indonesia [6,7]. Only 3% were screening detected.…”
Section: Total 193mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, 100 and 250 mg/kg of genistein in the diet dramatically reduced metastasis of PC3-M cells in mice without affecting tumor volume (Lakshman et al, 2008). It is well established that men in Asian countries consume more soy products and have a lower risk of prostate cancer (Chen et al, 2014). A study of Japanese men in Los Angeles county found the risk of prostate cancer in immigrants increased to the levels of American born men, suggesting an environmental cause (Shimizu et al, 1991).…”
Section: Phytoandrogensmentioning
confidence: 99%
“…There are differences between Asian and Western populations 4 and the relationship between PSA level and PCa detection rate may thus differ between these populations as summarized in a recent review. 5 In this study, we aim to determine the characteristics of Chinese men undergoing initial prostate biopsy and evaluate the relationship between PSA level and the detection rate of PCa and HGPCa in a nationwide, multicenter biopsy cohort.…”
Section: Introductionmentioning
confidence: 99%